(untitled) (Sains Humanika, 2015)
In this globalized era, flexibility supply chain and organizational performance are increasing in the automotive industry. The objectives of this paper are to explore and perform structural analysis of Flexibility Supply Chain (FSC) construct. Data were obtained from 243 top management posts among Malaysian automotive suppliers. This paper presents the results of the Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA), and reliability analysis, which are empirically verified and validated. A set of assessment measurement of FSC is expected to be suitable to improve the competitiveness and selected characteristics. The results show that two FSC constructs are acceptable for further analysis. The paper also proposes the future direction at the end of this research.